Perancangan Sistem Informasi Data Stock Controlling dengan Metode EOQ - Riskian Tahmid; Fajrul Islami; Mutiana Pratiwi; Ulya Ilhami Arsyah (Jurnal Teknologi, 2019)
Information  thecnology  development  is  quickly  even  in  outlying  places  that  are  never  feeld  its benefit  before,  but  nowdays  they  can  deeply  enjoy  able  with  information  thecnology  serves  in  an  online manner.  The  business  are  established  and  progressed  usually  organized  their  supply  management  there  (in the business). Previously PT. MUTIA MULIA PADANG has difficulty in the supply of the management be cause of manual character.Controlling inventory or inventory management right is not easy. But if too little inventory results in the risk of inventory shortage, as they often can not be imported goods inventory stating sudden  cessation  of  the  production  process,  delays  in  profits,  even  loss  of  customers.It  would  require  an inventory  application  to  manage  inventory  control,  then  the  company's  needs  will  bemet  with  swift  and precise,  so  as  to  control  inventory.  With  the  report  in  the  form  of  file  storage  can  allow  minimize  the potentially fatal errors, such as losing records. This application is built using the programming language PHP and MySQL, which assisted with modeling UML (Unified Modeling Language)